Vulnerability Mapping of the Hashtgerd Aquifer Using DRASTIC Method and Sensitivity Analysis - Fakhrodin Azad Shahraki; Abdolvahed Aghasi; Farzad Azad Shahraki; Alireza Zarei (آب و فاضلاب, 2010)
It is more expensive to remove pollution from polluted groundwater than to prevent it; hence, tools are sought that help managers prevent groundwater pollution. One such tool is the aquifer vulnerability mapping which is used to specify the most vulnerable parts of an aquifer.  In this research, the vulnerability map of the Hashtgerd aquifer was investigated. Irrigation return flow polluted by nitrate fertilizers, rural and urban wastewater, and industrial wastewater were found to be the main sources of pollution in the study area. The DRASTIC index was used and two methods of sensitivity analysis were performed on the results to ensure proper weights had been assigned to effective parameters. Then, Hashtgerd vulnerability map was compared with the relevant nitrate map to find a relatively acceptable tolerance. The results indicate that the highest vulnerability potential was of the medium class. The northern part of the study area has a high vulnerability potential while its southern stretches exhibit the lowest.